(untitled) (Al-Mukhtar Journal of Basic Sciences, 2026)
The Menai Strait, a tidal channel in northern Wales, represents a unique and dynamic marine environment where strong tidal currents drive significant changes in seabed geomorphology and sediment distribution. This study aims to investigate these changes using a combination of Single Beam Echo Sounder (SBES) data collected over seven years (2007–2014) and Multibeam Echo Sounder (MBES) data acquired over two years (2011–2012). The SBES data provide a long-term perspective on water depth variations, while the MBES data offer high-resolution insights into sedimentation rates and geomorphological processes. Advanced geospatial analysis tools, including ArcGIS, were utilized to process and interpret the bathymetric data. Hillshade and slope analyses of MBES datasets revealed distinct patterns of sediment deposition and erosion, driven by tidal dynamics. The study identified significant sediment accumulation in the central channel and pronounced erosion along the Strait’s edges, which correlates with varying tidal velocities and substrate types. Sand wave features observed in the MBES data highlighted dynamic sediment transport mechanisms, with changes in wave morphology indicating active seabed reworking processes. The findings underscore the effectiveness of integrating SBES and MBES data for monitoring seabed geomorphological changes in complex tidal environments. The study also highlights the necessity of tidal corrections and spatial analysis tools to enhance the accuracy and reliability of bathymetric surveys. By providing a detailed understanding of sedimentary processes in the Menai Strait, this research contributes valuable insights into the broader study of coastal and marine geomorphology. These results not only inform future studies on the impact of climate change and anthropogenic activities but also aid in developing sustainable management strategies for similar tidal environments worldwide.